Development of methodology and assessment of ecological safety of the EAEU and CIS regions in the context of sustainable development - Svetlana Demidova; Michael Balog; Tatiana Chircova; Anastasia Kulachinskaya; Svetlana Zueva; Irina Akhmetova; Svetlana Ilyashenko (Economies, 2021)
The trends of sustainable development and green agenda transform the production processes, leading industries, and regional markets, and reveal objective contradictions in ensuring the ecological safety of certain territories. This study aims to develop a methodology and assess ecological safety at aggregated system levels, taking into account natural and socioeconomic factors as well as the factor of human capital development with specification of the place of ecological safety in the concept of sustainable development. The objects of empirical research are the EAEU and CIS countries for the period 2010-2019, as well as 85 Russian regions. The scientific research toolkit is based on the methods of structural-logical, economical-statistical, and comparative analyses, and expert judgments. The concepts of sustainable development and human capital and the theory of the national school of ecological safety are analyzed using the systematic approach. The mixed methodological approach showed the interconnection of four approaches of assessing ecological safety (technogenic, environmental, institutional, resource-based). The authors developed a method for assessing ecological safety taking into account the contribution of human capital. The assessment results are typologized and grouped according to the dynamic trend. For the majority of the considered countries, changes in the level of ecological safety correlate with changes in socioeconomic indicators. The same trend is observed when considering the Russian regional formations. The contribution of human capital was recorded to a lesser extent. For several regions, the increased number of objects polluting the environment is accompanied by a decreased volume of polluting emissions into the atmosphere.
Keywords: 330; circular economy; ecological safety; environment; environmental policy; green economy; human capital; sustainable development